Current Status of Glycemic Control of Patients with Diabetes in Korea: The Fifth Korea National Health and Nutrition Examination Survey - Jeon, Ja Young; Kim, Dae Jung; Ko, Seung-Hyun; Kwon, Hyuk-Sang; Lim, Soo; Choi, Sung Hee; Kim, Chul Sik; An, Jee Hyun; Kim, Nan Hee; Won, Jong Chul; Kim, Jae Hyeon; Cha, Bong-Yun; et al. (Diabetes & metabolism journal, 2014)
The Korea National Health and Nutrition Examination Survey (KNHANES) III (2005) reported that 22.9% of individuals with diabetes have a glycated hemoglobin (HbA1c) <6.5% and that 43.5% have an HbA1c <7%. We investigated the levels of glycemic control and the factors associated with glycemic control using data from the KNHANES V (2010 to 2012). Subjects with diabetes diagnosed by a physician or those taking antidiabetic medications were classified as individuals with known diabetes. Of 1,498 subjects aged ≥30 years with diabetes, we excluded 157 individuals who were missing HbA1c data. A total of 1,341 subjects were included in the final analysis. The prevalence of known diabetes was 7.7% (n=1,498, estimated to be 2.32 million people). The proportions of well-controlled diabetes meeting a HbA1c goal of <6.5% and <7% were 27% and 45.6%, respectively. HbA1c increased as the duration of diabetes increased. HbA1c in subjects with a duration of diabetes ≤5 years was lower than in subjects with a duration >5 years. HbA1c in the group taking only oral hypoglycemic agents (OHAs) was significantly lower than that in the group administered only insulin or OHA and insulin in combination. In logistic regression analysis, a longer duration of diabetes, insulin use and the absence of chronic renal failure were associated with HbA1c levels >6.5%. The level of adequate glycemic control was similar to but slightly improved compared with previous levels. The glycemic control of long-standing diabetes patients is more difficult even though they receive insulin treatment.